2018
DOI: 10.1007/s10067-018-4018-1
|View full text |Cite
|
Sign up to set email alerts
|

Imatinib mesylate use in refractory eosinophilic granulomatosis with polyangiitis: a literature review and a case report

Abstract: Recent advances in pharmacology have greatly expanded the drug repertoire for treatment of anti-neutrophil cytoplasmic antibodies (ANCA)-associated vasculitis. Eosinophilic granulomatosis with polyangiitis (EGPA) is a rare multisystemic disorder, a type of the ANCA-associated vasculitis. Important features of this disease are eosinophilia and anti-myeloperoxidase ANCA presence in around 30-70% of patients. Primary therapy of EGPA includes steroids and cytotoxic drugs, e.g., cyclophosphamide, azathioprine, or m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…In fact, this drug has been reported as arthritis suppressor and inhibitor of IL-6 and other pro-inflammatory cytokines according to murine models [15,16]. In this regard, positive effects have been observed lowering inflammation in patients diagnosed with rheumatoid arthritis [17][18][19], asthma [20] and other chronic inflammatory disorders such as Crohn's disease [21,22] and refractory eosinophilic granulomatosis with polyangiitis [23]. Likewise, imatinib has been linked to improving pulmonary endothelial barrier dysfunction and edema observed in acute lung injury and sepsis [24,25].…”
mentioning
confidence: 98%
“…In fact, this drug has been reported as arthritis suppressor and inhibitor of IL-6 and other pro-inflammatory cytokines according to murine models [15,16]. In this regard, positive effects have been observed lowering inflammation in patients diagnosed with rheumatoid arthritis [17][18][19], asthma [20] and other chronic inflammatory disorders such as Crohn's disease [21,22] and refractory eosinophilic granulomatosis with polyangiitis [23]. Likewise, imatinib has been linked to improving pulmonary endothelial barrier dysfunction and edema observed in acute lung injury and sepsis [24,25].…”
mentioning
confidence: 98%
“…Another retrospective study demonstrated that PDGF can be used as a marker for the clinical diagnosis of cerebral amyloid angiopathy-related inflammation/vasculitis [ 18 ]. In line with these, imatinib mesylate, a PDGFR tyrosine kinase inhibitor, has been shown to have therapeutic potential for refractory eosinophilic granulomatosis with polyangiitis and giant cell arteritis [ 24 , 25 ]. These studies emphasize the potential role of PDGF in vasculitis.…”
Section: Discussionmentioning
confidence: 99%
“…It was previously shown that Tcells and associated cytokines such as IL-6, IL-10, IL-12, IL-23 and type I interferons play an important role in of AAV pathogenesis via JAK/STAT pathway activation (28,29). Imatinib mesylate which is a tyrosine kinase inhibitor was recently reported to be effective in the treatment of a case with EGPA (30). Recently, a case series including 10 patients with AAV (6 with GPA, 3 with MPA and 1 with EGPA) reported the efficacy and safety of TOF.…”
Section: Small Vessel Vasculitismentioning
confidence: 99%